While global FDI fails, China's outward FDI doubles - Ken Davies (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2009)
This Perspective examines the drivers behind the surge in FDI from China in 2008 and the salient features of this outward investment. Davies also discusses how the global financial crisis is affecting China's outward FDI.
Keywords: 330